Perlindungan Anak Usia Sekolah Terhadap Program Keluarga Harapan Mangepong Jeneponto - Awaluddin (Jurnal Berita Sosial, 2022)
Social protection for school-age children through the family hope program to improve family welfare. The type of research used is qualitative with social welfare and sociological approaches. The data sources in this study are primary data sources and secondary data sources, primary data sources include eight informants, including the head of the PKH group, the village head of Mangepong, parents of school-age children, and school-age children. Secondary data sources are in the form of interviews, documentation tools, stationery and tape recorders. The results of this study are school-age children in Mangepong Village have social protection in the Family Hope Program (PKH). Social protection in the Family Hope Program in the Village is aimed at children who are currently attending elementary, middle, and high school. The social conditions of school-age children in Mangepong Village are everything related to the situation or condition of school- age children, where these conditions are divided into three categories, namely health conditions, parents’ economic conditions, and school-age children’s routines. School-age children in Mangepong Village receive education guarantees from PKH. The education guarantee is in the form of direct cash assistance. Aimed at school-age children in elementary, junior high, and high school. Assistance for elementary school children is Rp. 125,000/3 months, junior high school children Rp. 187,000/3 months, and high school students Rp. 250,000/3 months. The donations were used to buy school supplies such as school clothes, shoes, books and learning tools. The routines of school-age children in Mangepong Village are all activities or activities carried out by school-age children, both in the school environment, and outside the school environment. These routines are learning, playing, and helping parents at home.